Combating Stigma in the Era of Monkeypox—Is History Repeating Itself?. (5th November 2022) - Bergman, Alanna; McGee, Kara; Farley, Jason; Kwong, Jeffrey; McNabb, Katherine; Voss, Joachim
Abstract: Men who have sex with men (MSM) and people with HIV (PWH) perceive, internalize, and experience significant stigma from family members, health care providers, and community members because of their sexual behaviors. The current monkeypox (MPX) outbreak is affecting both communities. The pandemic has spread to 89 countries with more than 31, 000 confirmed cases, and global agencies are concerned about how the disease is portrayed in the media. This article will introduce MPX and its associated stigmas, providing a brief theoretical perspective on adaptive behaviors and nursing interventions to mitigate stigma. This is followed by a case-based description of the current experiences of an MSM with MPX. We will discuss stigma prevention strategies from an adaptation and mitigation perspective. We conclude with how nurses can contribute to stigma prevention for individuals with MPX.